Infants’ Implicit Rhyme Perception in Child Songs and Its Relationship With Vocabulary - Hahn, Laura E.; Benders, Titia; Fikkert, Paula; Snijders, Tineke M. (Frontiers in Psychology, 2021)
Rhyme perception is an important predictor for future literacy. Assessing rhyme abilities, however, commonly requires children to make explicit rhyme judgements on single words. Here we explored whether infants already implicitly process rhymes in natural rhyming contexts (child songs) and whether this response correlates with later vocabulary size. In a passive listening ERP study, 10.5 month-old Dutch infants were exposed to rhyming and non-rhyming child songs. Two type of rhyme effects were analysed: 1) ERPs elicited by the first rhyme occurring in each song (rhyme sensitivity) and 2) ERPs elicited by rhymes repeating after the first rhyme in each song (rhyme repetition). Only for the latter a tentative negativity for rhymes from 0 to 200 ms after the onset of the rhyme word was found. This rhyme repetition effect correlated with productive vocabulary at 18 months-old, but not with any other vocabulary measure (perception at 10.5 or 18 months-old). While awaiting future replication, the study indicates precursors of phonological awareness already during infancy and with ecologically valid linguistic stimuli.